2009
DOI: 10.1590/s1808-18512009000200002
|View full text |Cite
|
Sign up to set email alerts
|

Correlação entre o número de parafusos e o percentual de correção no tratamento cirúrgico da escoliose neuromuscular

Abstract: OBJETIVO: avaliar se existe relação entre o número de parafusos pediculares (densidade de parafusos) e o percentual de correção da curva principal no tratamento cirúrgico das escolioses neuromusculares. MÉTODOS: foram avaliados, retrospectivamente, 55 pacientes portadores de escoliose neuromuscular submetidos ao tratamento cirúrgico por meio de artrodese exclusivamente pela via posterior. Foram analisados o valor da curva pré-operatória, o percentual de correção e o valor da curva pós-operatória nas radiografi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…There was no association between screw density and outcome for the Lenke 5 curves. Daher et al, 7 concluded that in the surgical treatment of neuromuscular scoliosis the correction of the curve increases as the implant density increases.…”
Section: Discussionmentioning
confidence: 99%
“…There was no association between screw density and outcome for the Lenke 5 curves. Daher et al, 7 concluded that in the surgical treatment of neuromuscular scoliosis the correction of the curve increases as the implant density increases.…”
Section: Discussionmentioning
confidence: 99%
“…As in other studies, it was noted that the presence of curves with high angular values and the need for surgical intervention did not seem to be related to sex. 13,14 Regarding the age of the individuals on the date of surgical intervention, we observed greater variability in the sample. The mean age found in our study was 13.9 years, similar to the data published in the study by Jaccard, 13 who reported a mean age of 11 years.…”
Section: Discussionmentioning
confidence: 77%
“…[10][11][12] Most studies correlate the presence of scoliosis with the degree of neurological involvement 2,[5][6][7] and few correlate the deformity with any type of functional classification such as the GMFCS. 1 In addition, no study correlates the type of deformity to motor function.…”
Section: Discussionmentioning
confidence: 99%